Biofilm characterisation of Mycoplasma bovis co-cultured with Trueperella pyogenes - Koji Nishi; Satoshi Gondaira; Yuki Hirano; Masahide Ohashi; Ayano Sato; Kazuya Matsuda; Tomohito Iwasaki; Takuya Kanda; Ryoko Uemura; Hidetoshi Higuchi (Veterinary Research)
Abstract Mycoplasma pneumonia, caused by Mycoplasma bovis (Mycoplasmopsis bovis; M. bovis), is linked with severe inflammatory reactions in the lungs and can be challenging to treat with antibiotics. Biofilms play a significant role in bacterial persistence and contribute to the development of chronic lesions. A recent study has shown that polymicrobial interactions between species are an important factor in biofilm formation, yet the precise mechanism of biofilm formation in M. bovis remains unknown. By assuming multiple pathogen infections in the bovine respiratory disease complex (BRDC), this study examined the characterisation of the polymicrobial relationship between M. bovis and Trueperella pyogenes (T. pyogenes) during biofilm formation. Autopsies were performed on four Holstein calves (two chronic Mycoplasma pneumonia calves and two control calves). Bacterium-like aggregation structures (> 10 μm), which were assumed to be biofilms of M. bovis in vivo, were observed adhering to the cilia in calves with Mycoplasma pneumonia. M. bovis released an extracellular matrix to connect with neighbouring bacteria and form a mature biofilm on the plate. Biofilm formation in the co-culture of M. bovis and T. pyogenes (strain T1: 1 × 105 and 1 × 106 CFU/well) significantly increased (p < 0.05 and p < 0.01; 64.1% and 64.8% increase) compared to that in a single culture of these bacteria. Furthermore, some large aggregates (> 40 μm), composed of M. bovis and T. pyogenes, were observed. The morphological characteristics of this biofilm were similar to those observed in vivo compared to a single culture. In conclusion, the polymicrobial interaction between M. bovis and T. pyogenes induces biofilm formation, which is associated with increased resistance to antimicrobial agents, and this exacerbates the progression of chronic Mycoplasma pneumonia.